Pengaruh Tingkat Inflasi, Peringkat Obligasi, Ukuran Perusahaan Terhadap Yield Obligasi Syariah Pada Sukuk Korporasi Yang Terdaftar Di BEI Periode 2018-2021 - Sifa Auliya, Rahma; Nuril Hidayati, Amalia (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The aim of this research was to examine the relationship between the influence of inflation rates, bond ratings, company size on sharia bond yeilds on corporate sukuk. The retuns obtained by investors are always fluctuating. Therefore, research is needed to find out more and see how much influence the variables used in this study have. The population used in this study were all bond companies on corporate sukuk that were traded on the Indonesia Stock Exchange (IDX) for the period 2018 to 2021. The sample used in this study were 7 companies on corporate sukuk bonds. The data analysis technique used is panel data regression analysis with quantitative research. The results of this study indicate that the inflation rate has a negative signifikan effect on sharia bond yields. Bond rating and company size also have a positive and significant effect on sharia bond yields on corporate sukuk listed on the Indonesia Stock Exchange (IDX). As well as the inflation rate, bond ratings, and company size have a large enough presentation in influencing sharia bond yeilds.